Assessing competence of mid-level providers delivering primary health care in India: a clinical vignette-based study in Chhattisgarh state - Samir Garg; Narayan Tripathi; Jayathra Datla; Tomas Zapata; Dilip S. Mairembam; Kirtti K. Bebarta; C. Krishnendhu; Hilde de Graeve (BMC, 2022)
Abstract Background The global commitment to primary health care (PHC) has been reconfirmed in the declaration of Astana, 2018. India has also seen an upswing in national commitment to implement PHC. Health and wellness centres (HWCs) have been introduced, one at every 5000 population, with the fundamental purpose of bringing a comprehensive range of primary care services closer to where people live. The key addition in each HWC is of a mid-level healthcare provider (MLHP). Nurses were provided a 6-month training to play this role as community health officers (CHOs). But no assessments are available of the clinical competence of this newly inducted cadre for delivering primary care. The current study was aimed at providing an assessment of competence of CHOs in the Indian state of Chhattisgarh. Methods The assessment involved a comparison of CHOs with rural medical assistants (RMAs) and medical officers (MO), the two main existing clinical cadres providing primary care in Chhattisgarh. Standardized clinical vignettes were used to measure knowledge and clinical reasoning of providers. Ten ailments were included, based on primary care needs in Chhattisgarh. Each part of clinical vignettes was standardized using expert consultations and standard treatment guidelines. Sample size was adequate to detect 15% difference between scores of different cadres and the assessment covered 132 CHOs, 129 RMAs and 50 MOs. Results The overall mean scores of CHOs, RMAs and MOs were 50.1%, 63.1% and 68.1%, respectively. They were statistically different (p < 0.05). The adjusted model also confirmed the above pattern. CHOs performed well in clinical management of non-communicable diseases and malaria. CHOs also scored well in clinical knowledge for diagnosis. Around 80% of prescriptions written by CHOs for hypertension and diabetes were found correct. Conclusion The non-physician MLHP cadre of CHOs deployed in rural facilities under the current PHC initiative in India exhibited the potential to manage ambulatory care for illnesses. Continuous training inputs, treatment protocols and medicines are needed to improve performance of MLHPs. Making comprehensive primary care services available close to people is essential to PHC and well-trained mid-level providers will be crucial for making it a reality in developing countries.